A new approach to sediment transport in the design and operation of irrigation canals - Depeweg, Herman. (UNESCO-IHE lecture note series., 2007)
Understanding the behavior and transport of sediment allows efficient planning and reliable water delivery schedules, and ensures the controlled deposition of sediments, making maintenance activities more manageable. This book presents a detailed analysis of sediment transport in irrigation canals, together with physical and mathematical descriptions of the behavior. The authors use a mathematical model to predict the sediment transport, deposition and entrainment rate for various flow conditions and sediment inputs. The model is particularly suitable for the simulation of sediment transport in irrigation canals where flow and sediment transport are determined by the operation of flow control structures.